Aplikasi Sistem Informasi Perkumpulan Kepala Keluarga Berbasis Sms Gateway (Studi Kasus: Wilayah RW-IV Kelurahan Kratonan) - Muchtar, Annisa Fitriana; , Umi Fadlilah, S.T., M.Eng (2015)
Each RT has policies and rules to achieve the goals in protecting its citizens. At each RT has a bevy of activities that are family heads formal (regular) and non-formal. In the execution did not escape the constraints of the existing constraints such as personnel, announcement or notification, Lost Communication (lack of communication), the establishment of a schedule, etc. Activity Information System Association of Family Head made based website using PHP programming language, HTML, using XAMPP as a database server, MySQL as the database, as well as servers Cloud SMS Gateway SMS Gateway. In the test phase using a questionnaire to get feedback and assessment of the system that has been designed. The questionnaire will be distributed to 11 respondents including 1 Admin, 10 residents (User). Activity Information System Association of Family Head is expected to emmbantu the citizens to know the information up to date via via SMS, assist in managing the meeting schedule and the schedule of patrolling and computing fines. The existence of this system can reduce the constraints Lost Communication and can more effectively and efficiently.